Effectiveness of Bezlotoxumab for Prevention of Recurrent Clostridioides difficile Infection Among Transplant Recipients. (4th June 2021) - Johnson, Tanner M; Howard, Amanda H; Miller, Matthew A; Allen, Lorna L; Huang, Misha; Molina, Kyle C; Bajrovic, Valida
Abstract: Background: Bezlotoxumab significantly reduces the incidence of recurrent Clostridioides difficile infection (CDI); however, limited data are available in solid organ transplant (SOT) and hematopoietic cell transplant (HCT) recipients. Methods: We conducted a single-center retrospective analysis comparing recurrent CDI in SOT and HCT recipients receiving standard of care alone (oral vancomycin, fidaxomicin, or metronidazole) or bezlotoxumab plus standard of care. The primary outcome was 90-day incidence of recurrent CDI, and secondary outcomes included 90-day hospital readmission, mortality, and incidence of heart failure exacerbation. Results: Overall, 94 patients received bezlotoxumab plus standard of care (n = 38) or standard of care alone (n = 56). The mean age was 53 years; patients had a median of 3 prior Clostridioides difficile episodes and 4 risk factors for recurrent infection. Most patients were SOT recipients (76%), with median time to index CDI occurring 2.7 years after transplantation. Ninety-day recurrent CDI occurred in 16% (6/38) in the bezlotoxumab cohort compared to 29% (16/56) in the standard of care cohort ( P  = .13). Multivariable regression revealed that bezlotoxumab was associated with significantly lower odds of 90-day recurrent CDI (odds ratio, 0.28 [95% confidence interval, .08–.91]). There were no differences in secondary outcomes, and no heart failure exacerbations were observed. Conclusions: In a cohort of primarily SOT recipients, bezlotoxumab was well tolerated and associated with lower odds of recurrent CDI at 90 days. Larger, prospective trials are needed to confirm these findings among SOT and HCT populations.